BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2006)
Challenging problems in Horticulture and Forest Pathology by R.C. Sharma and J.N. Sharma, Indus PublishingCompany, New Delhi, 452 pp, Rs. 1200.00 Value addition to weather data Advisory Service to Farmers, Editor : V. Rajagopal and S. Naresh Kumar, 102 pp., Rs. 230.00, US$ 20